2023
DOI: 10.3390/ijerph20126168
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Times of Pandemic Crisis among Italian Children: A Systematic Review

Abstract: Several studies underlined the negative effects of forced social isolation on emotional processes in younger population. The current study aimed to review existing evidence of the pandemic’s impact on the emotional regulation of Italian children aged 0–12 years in order to identify personal and contextual factors that may adversely impact their developmental process. Different electronic databases (Web of Science, APA PsycInfo, APA PsycArticles, MEDLINE, Psychology and Behavioral Sciences Collection, and Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 110 publications
1
6
0
Order By: Relevance
“…Furthermore, a relationship between school closure and an increase in emotional and behavioral difficulties is once again confirmed. Our results are also in line with a recent systematic review of Italian K12 students during school closure [88]. Their results confirmed an increase in emotional dysfunction demonstrated by an increase in anxiety, anger, difficulty concentrating, and even sleep disturbances.…”
Section: Plos Onesupporting
confidence: 92%
“…Furthermore, a relationship between school closure and an increase in emotional and behavioral difficulties is once again confirmed. Our results are also in line with a recent systematic review of Italian K12 students during school closure [88]. Their results confirmed an increase in emotional dysfunction demonstrated by an increase in anxiety, anger, difficulty concentrating, and even sleep disturbances.…”
Section: Plos Onesupporting
confidence: 92%
“…According to some research, it is younger parents who present more problems [44,82], while other studies found it is older ones [9]. With respect to socioeconomic status, strain arising from financial problems increased parental stress; precarious and unfavorable economic conditions, such as low SES, may, therefore, be associated with a higher risk of both parental and child maladjustment [15,44,59].…”
Section: Current Studymentioning
confidence: 99%
“…With respect to children, available data from the pandemic indicate a significant increase in emotional symptoms, such as irritability, anger, anxiety, mood alterations, sleep disturbances, feeding-related issues, and hyperactivity [6,[10][11][12][13][14][15].…”
Section: Introduction 1the Impact Of the Pandemic On Children's Emoti...mentioning
confidence: 99%
See 2 more Smart Citations